Analysis of The Impact of Unemployment for Individual, Social, and Economics - HARYONO, SISWOYO; DJOHANTINI, SITI NOORDJANNAH (The journal of contemporary issues in business and government, 2021)
Unemployment is one of the social problems in economic development. The unemployment problem is an individual problem and a state problem that must be resolved to realize economic growth. This research is a descriptive study using a qualitative approach. The purpose of using this approach is so that researchers can obtain a complete picture of the problems formulated by focusing on the process and the search that is studied is more comprehensive, in- depth, natural, and as it is. This study uses interview and document methods by collecting and classifying data according to the type of data to determine how the actual impact of unemployment in Indonesia is. This study uses the Milles and Huberman data analysis method, namely "the technique of data analysis which consists of 3 activity streams, namely: (1) data condensation, (2) data presentation, and (3) concluding / verification. Based on the research results, it can be seen that the majority of unemployed feel a negative impact on themselves and the environment. For a country's economy, the impact of unemployment is that the country cannot promote economic growth both in the long term and in the short term.